Pengembangan Seni Hidangan Alternatif dan Terinspirasi pada Kader Posyandu Balita Sesuai Kandungan Gizi Isi Piringku di Desa Karangsono Kabupaten Jember - Saskia Nadhira Ayudani; Khuliyah Candraning Diyanah; Aditya Sukma Sukma Pawitra; Nur Rahma Febriani; F. Himmatul Aliyah; Ardan Saputra; Na'ilah Putri Az'zahroh; Muhammad Ilham Rofiudin; Triana Pristafania; Akbar Maulana Azhari; Nabila Berlianny Nur Anisa; Ria Lusiandari; Tri Wahyu Suprayogi (Universitas Nurul Jadid, 2024)
Stunting poses a serious health issue in Indonesia. In 2022, the national prevalence of stunting stood at 22.6%, exceeding the World Health Organization's requirement of below 20%. According to the Indonesian Nutrition Status Survey (SSGI) 2022 by the Ministry of Health, Jember Regency has the highest prevalence of stunted toddlers in East Java, reaching 34.9% or approximately 35,000 toddlers. To address the stunting problem, health efforts are being made through the prevention of stunting diseases with the implementation of the